2017
DOI: 10.1371/journal.pone.0187681
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tillage practice on soil structure, N2O emissions and economics in cereal production under current socio-economic conditions in central Bosnia and Herzegovina

Abstract: Conservation tillage is expected to have a positive effect on soil physical properties, soil Carbon (C) storage, while reducing fuel, labour and machinery costs. However, reduced tillage could increase soil nitrous oxide (N2O) emissions and offset the expected gains from increased C sequestration. To date, conservation tillage is barely practiced or studied in Bosnia and Herzegovina (BH). Here, we report a field study on the short-term effects of reduced (RT) and no tillage (NT) on N2O emission dynamics, yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…Tillage management had little impact on N 2 O emissions in this study (Table 2 and Table 3) in line with earlier work examining CT and RT systems (Abdalla et al, 2010;Liu et al, 2016). Peak N 2 O emissions that were found in the MT and ST but not in the CT treatments coincided with a higher WFPS (>70%) and higher temperatures (>10°C) as noted in previous studies (Adviento-Borbe et al, 2007;Abdalla et al, 2010;Žurovec et al, 2017;O'Neill et al, 2020). This indicates that denitrification is the main source of N 2 O production and the N 2 O emissions are largely dependent on the extent of soil anaerobiosis.…”
Section: Crop Management and Ghg Emissionssupporting
confidence: 91%
“…Tillage management had little impact on N 2 O emissions in this study (Table 2 and Table 3) in line with earlier work examining CT and RT systems (Abdalla et al, 2010;Liu et al, 2016). Peak N 2 O emissions that were found in the MT and ST but not in the CT treatments coincided with a higher WFPS (>70%) and higher temperatures (>10°C) as noted in previous studies (Adviento-Borbe et al, 2007;Abdalla et al, 2010;Žurovec et al, 2017;O'Neill et al, 2020). This indicates that denitrification is the main source of N 2 O production and the N 2 O emissions are largely dependent on the extent of soil anaerobiosis.…”
Section: Crop Management and Ghg Emissionssupporting
confidence: 91%
“…Soil tillage results in changes in the soil structure, soil aeration, microbial activity, rate of residue decomposition and loss of soil organic matter from the system, as well as soil temperature and moisture [127,133]. It was also found that the presence or absence of tillage, the tillage period and tillage implements had an influence on N 2 O emissions [131,134].…”
Section: Tillage Systemsmentioning
confidence: 99%
“…We suggest that the time span required for satisfactory preventive G. quadriradiata control may be shortened by using false seedbed strategies that minimally disturb the soil, as tested in experiment 1. That the success of a false seedbed strategy did not depend on the number of passes or number of tillage passes per tillage event (see Discussion about single and double hoeing) is encouraging, because tillage intensive systems may have a negative effect on soil physical properties, soil carbon storage, and fuel, labour and machinery costs (Zurovec et al ., ).…”
Section: Discussionmentioning
confidence: 97%